Faktor-Faktor Yang Mempengaruhi Tindakan Perawat Dalam Penanganan Kedaruratan Fraktur Di Ruang Instalasi Gawat Darurat Di Rumah Sakit TK. II Pelamonia Makassar - Nurun Salaman Alhidayat; Dwi Esti Handayani; Nur Halimah; Zakariati Zakariati (Jurnal Kesehatan Medika Udayana, 2022)
Background: The emergency Room (IGD) is one of the main doors in emergency assistance in patient survival. One of the conditions that require emergency treatment is a fracture. Purpose: This research aims to determine the factors that influence the actions of nurses in handling emergency fracture patients. Methods:The research design used was observational non-experimental with a cross-sectional approach. The research sample is the nurse in the Emergency Unit. Data processing was arranged by the data group and data analysis using the SPSS program computer and presented in tables and frequencies Results: The results showed that there was a significant relationship between the level of knowledge, level of experience and level of training in emergency management (<0.05) of fracture patients at Tk.II Pelamonia Hospital Makassar. Conclusion: the factors that influence the emergency management of fracture patients are knowledge, training and experience.